Role of restorativeness in improving psychological well-being of uiversity students - Mohd Yusli, Nurul Ain Nabilla; Roslan, Samsilah; Zaremohzzabieh, Zeinab; Ghiami, Zeinab; Ahmad, Noorlila (Frontiers Research Foundation, 2021)
Many university students experience high levels of study-related fatigue, hence, necessitating opportunities for restoration. They could potentially benefit from campus-based physical activities that provide them with effective restoration breaks and allow them to return to their studies cognitively refreshed. Thus, a cross-sectional study was conducted to assess the association between perceived restorativeness among postgraduates and their psychological well-being by using the four constructs of Kaplan's attention restoration theory (ART): fascination, being away, extent, and compatibility. In this study, nature view windows were also used as a moderator. Malaysian postgraduate students [n = 192; 94 females; age in years (M = 30.64, SD = 2.73)] completed the Ryff's scale of psychological wellbeing (PWB) and perceived restorativeness scale for activity (PRAS). This study used the partial least squares-structural equation model (PLS-SEM) to examine these relationships. The results demonstrate that three ART constructs, namely, being away, fascination, and compatibility, are significant predictors of psychological well-being across the sample size. Furthermore, for participants who reside in university dormitories, windows that overlook nature can enhance the relationship of being away, compatibility, and fascination to psychological well-being, compared with those with less natural views. Thus, this study confirmed the moderating effect of nature view windows and provided insight into the ART constructs that facilitate and enhance restorative experiences. By strengthening ART with additional factors, this study has also contributed toward the improvement of the psychological well-being of university students.